Islamic Religion-Focused Coping Method as a Strategy to Manage Work Stress/ Metode Islamic Religion-Focused Coping sebagai Strategi Mengatasi Stres Kerja - Triwahyuni, Atikah; Kadiyono, Anissa Lestari (Psikoislamika: Jurnal Psikologi Islam, 2020)
Abstract: Islamic Religion-Focused Coping is a strategy as an effort to manage work stress by using religious belief and demonstrating religious behavior in order to prevent or reduce the consequences of work stress. Work stress in companies has become an important issue to observe due to the emergence of demand to be more efficient at work. This research was conducted to describe the Islamic religion-focused coping in garment company employees who experienced work stress. The research design used was quantitative-descriptive method through questionnaire. The participants of this study were 82 employees who went through screening stage with a stress diagnostic survey to measure work stress. The result showed that the most prominent source of stress among 75 employees with work stress at moderate and high levels resulted from group of colleagues. The instrument used was a questionnaire developed by Pargament to examine employee Islamic religion-focused coping. The final result showed that a total of 86% employees used Islamic religion-focused coping in managing their work stress. On its dimension, employees often used religious belief (believing that Allah SWT would help solve every problem) and religious behavior (praying and reciting Al-Quran). Demographic factors in this research also affected how an employee used the coping, namely age development. This indicates that the elder the employees are, the more they use Islamic religion-focused coping to reduce work stress and maintain productivity at work.Keywords: Islamic Religion-Focused Coping; Productivity; Work StressAbstrak: Islamic religion-focused coping merupakan strategi yang berlangsung sebagai bentuk usaha mengelola stres kerja dengan cara menggunakan kepercayaan agama (religious belief) dan melakukan kegiatan keagamaan (religious behavior) untuk mencegah atau mengurangi konsekuensi stres kerja. Masalah stres kerja di dalam perusahaan menjadi gejala yang penting diamati sejak tuntutan untuk lebih efisien di dalam pekerjaan. Penelitian ini dilakukan untuk memaparkan Islamic religion-focused coping pada karyawan perusahaan garmen yang mengalami stres kerja. Rancangan penelitian ini yakni metode kuantitatif dengan metode deskriptif melalui kuesioner. Partisipan penelitian yakni karyawan sebanyak 82 orang, yang kemudian melalui tahap screening dengan stres diagnostic survey untuk mengukur stres kerja. Didapatkan data sebanyak 75 karyawan yang merasakan stres kerja di taraf moderat dan tinggi, sumber stres yang paling menonjol berasal dari kelompok rekan kerja. Alat ukur yang digunakan yakni kuesioner yang dikembangkan oleh Pargament untuk melihat bagaimana gambaran Islamic religion-focused coping terhadap karyawan. Hasil akhir menunjukkan bahwa sebanyak 86% karyawan menggunakan Islamic religion-focused coping dalam menanggulangi stres kerja yang dialami. Pada dimensinya, karyawan sering menggunakan religious belief (percaya bahwa Allah SWT akan membantu setiap masalah yang datang) dan religious behavior (shalat, berdoa, dan membaca Al-Quran). Faktor demografi pada penelitian ini juga memengaruhi cara seseorang melakukan coping, yaitu perkembangan usia karyawan. Semakin dewasa usia karyawan, semakin sering menggunakan Islamic religion-focused coping untuk mengurangi stres kerja dan menjaga produktivitas saat bekerja.Kata Kunci: Islamic Religion-Focused Coping; Produktivitas; Stres Kerja